Altered Expression of Glucocorticoid Receptor and Neuron-Specific Enolase mRNA in Peripheral Blood in First-Episode Schizophrenia and Chronic Schizophrenia - Liu, Yong; Tang, Yamei; Li, Cunyan; Tao, Huai; Yang, Xiudeng; Zhang, Xianghui; Wang, Xuyi (Frontiers in Psychiatry, 2020)
Abstract Background: It is well-known that altered hypothalamus-pituitary-adrenal (HPA) axis process has an important role in the neurodegenerative process in schizophrenia (SZ). However, this neurodegenerative mechanism has not been clarified in SZ. Therefore, the main purpose of this study was to determine HPA axis damage in the first-episode, unmedicated schizophrenia (FES) patients and chronic schizophrenia (CSZ) patients in comparison with healthy controls (HC) by means of quantitative analysis of the peripheral blood mRNA expression of glucocorticoid receptor (GR), GR transcripts containing exons 1B (GR-1B) and neuron specific enolase (NSE) genes and serum cortisol and NSE, a specific serum marker for neuronal damage. Methods: In the present study, 43 FES patients, 39 CSZ and 47 HC were included. The peripheral blood mRNA expressions for GR, GR 1B and NSE genes were determined by real-time quantitative polymerase chain reaction (RT-qPCR). Serum cortisol and NSE were analyzed by electrochemiluminescence immunoassay technique. Results: Levels of GR mRNA were significantly lower in FES and CSZ than that in HC. The expression of GR-1B mRNA was significantly decreased in CSZ when compared with that in HC. Levels of NSE mRNA were significantly lower in CSZ than that in FES patients or HC patients. CSZ patients showed significantly lower cortisol concentrations than FES and HC patients. FES patients showed significantly higher NSE concentrations than CSZ and HS. Conclusion: Our findings support that there is disrupted HPA axis system in the SZ, and suggest that CSZ patients suffer a greater HPA axis damage than FES patients. Meanwhile, our research implicated underlying GR mRNA dysregulation in SZ and the potential importance of the functional GR-1B transcription in CSZ.